2018
DOI: 10.1111/sum.12460
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil microbial biomass, diversity and metabolic activity to biochar applications in managed poplar plantations on reclaimed coastal saline soil

Abstract: With its relatively high stability, biochar has been suggested as a means to mitigate climate change through carbon fixation and improve the physicochemical properties of soils. However, our understanding of the effects of biochar on soil microbial diversity and their metabolic activity remain unclear. In order to elucidate how the application of biochar to plantation soils influences microbial biomass and functional diversity (using Biolog EcoPlatesTM), we conducted an experiment to investigate changes in soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Biochar can influence soil microbial activity due to changes in labile carbon and soil properties (Herrmann et al 2019;Yu et al 2019). Some studies suggest that addition of biochar in soil may increase (Khadem and Raiesi 2017a;Beheshti et al 2018;Song et al 2018;Herrmann et al 2019) or decrease the microbial activity (Xu et al 2018), while other studies have reported that biochar application to soil has no effect on the soil microbial activity (Rutigliano et al 2014;Elzobair et al 2016). These contradictory results may be due to variety of the soil types, biochar biomass type, pyrolysis conditions, and the addition rate used in different studies (Beheshti et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biochar can influence soil microbial activity due to changes in labile carbon and soil properties (Herrmann et al 2019;Yu et al 2019). Some studies suggest that addition of biochar in soil may increase (Khadem and Raiesi 2017a;Beheshti et al 2018;Song et al 2018;Herrmann et al 2019) or decrease the microbial activity (Xu et al 2018), while other studies have reported that biochar application to soil has no effect on the soil microbial activity (Rutigliano et al 2014;Elzobair et al 2016). These contradictory results may be due to variety of the soil types, biochar biomass type, pyrolysis conditions, and the addition rate used in different studies (Beheshti et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biochar can alter soil properties, therein C/N is an important factor, and further mediated soil microbial metabolism and shifted community composition (Zheng et al., 2016). Another possible explanation of positive priming effect is that biochar can support the growth of microbial communities because of its high specific surface area, which can provide a suitable living space for microbial communities as well as able to store enough nutrients that can improve the growth of organism (Fiorentino et al., 2019; Xu et al., 2018). Further, the interactions between native SOC and soil mineral matrix might be altered by biochar addition, especially containing high amounts of mineral in surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Soil organic carbon and microbial properties could be stimulated by various environment factors, such as substrate and oxygen availability, soil moisture, temperature, and soil texture (A' Bear et al 2014;Ma et al 2016;Maenhout et al 2018;Xu et al 2018). To our knowledge, few studies have considered the relationships between the groups of SOC, soil microorganisms, and enzyme activities in the rhizosphere microenvironment under elevated CO 2 and Cd stress.…”
Section: Relationship Between Soil Organic Carbon Fractions and Micromentioning
confidence: 99%